Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4236/ijaa.2018.81002
|View full text |Cite
|
Sign up to set email alerts
|

Newton’s and Einstein’s Gravity in a New Perspective for Planck Masses and Smaller Sized Objects

Abstract: Here we derive Newton's and Einstein's gravitational results for any mass less than or equal to a Planck mass. All of the new formulas presented in this paper give the same numerical output as the traditional formulas. However, they have been rewritten in a way that gives a new perspective on the formulas when working with gravity at the level of the subatomic world. To rewrite the well-known formulas in this way could make it easier to understand the strengths and weaknesses in Newton's and Einstein's gravita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Haug has, in a series of papers [11][12][13], suggested that Newton's gravitational constant is a composite constant of the form…”
Section: Why Newton's Gravitational Constant Is a Composite Constantmentioning
confidence: 99%
“…Haug has, in a series of papers [11][12][13], suggested that Newton's gravitational constant is a composite constant of the form…”
Section: Why Newton's Gravitational Constant Is a Composite Constantmentioning
confidence: 99%
“…− mc (5) and when v << c, this can be very well approximated by the first term of a Taylor series expansion…”
Section: New Momentum Definitionmentioning
confidence: 99%
“…We claim that this will also hold for photons. The key is to combine it with Haug's maximum velocity [3][4][5][6][7] of matter vmax = c 1 −…”
Section: New Momentum Definitionmentioning
confidence: 99%
“…We claim that this will also hold for photons. The key is to combine it with Haug's maximum velocity [10,[12][13][14][15] of matter vmax = c 1 − l 2 p λ 2 . As discussed in previous papers, in the special case of the Planck mass particle, the maximum velocity is zero vmax = c 1 − l 2 p l 2 p = 0 (9) This sounds absurd, but in our view it represents the collision point between two photons.…”
Section: New Momentum Definitionmentioning
confidence: 99%